Background sensing control for planning agents working in the real world. (17th December 2009) - Hayashi, Hisashi; Tokura, Seiji; Ozaki, Fumio; Doi, Miwako
Online planning agents can adapt to the dynamic environment by continuously modifying plans during the plan execution. This adaptability of the online planning agents is based on the assumption that they can recognise the events happening in the environment. However, robotic agents working in the real environment cannot obtain necessary information from the outer world by simply turning all sensors on while executing a plan. They have to actively sense the world by changing the direction of the sensor to the target, analysing the raw sensor data, extracting important information and recognising the situation. Online planning is useless if they cannot obtain necessary information from the world. Therefore, it is crucial to decide what events the agent needs to recognise in the background while executing a plan. To solve this problem, this paper introduces a new background sensing control technique by which planning agents can effectively observe the real environment and obtain important information when necessary during the plan execution.